The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2478/cee-2021-0058
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Indoor Environment in the Intelligent Building

Abstract: Currently, thermal comfort and indoor air quality are essential elements in designing modern and intelligent buildings or improving existing ones, so that they would provide proper indoor conditions. The article focuses on the thermal sensations of the students of Kielce University of Technology and determining whether the given parameters of the internal environment contributed to their well-being. 164 people aged 16 - 24 participated in the study, which was conducted with the use of a microclimate meter and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(25 reference statements)
3
7
0
Order By: Relevance
“…Recent studies [3] on thermal comfort in a smart building have shown that there is a difference between subjective feelings and actual results. Similar conclusions were observed in the authors [4,5]. There are studies [6] showing that thermal comfort is influenced by the following factors: carbon dioxide concentration and relative humidity, air temperature and volatile organic compounds.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recent studies [3] on thermal comfort in a smart building have shown that there is a difference between subjective feelings and actual results. Similar conclusions were observed in the authors [4,5]. There are studies [6] showing that thermal comfort is influenced by the following factors: carbon dioxide concentration and relative humidity, air temperature and volatile organic compounds.…”
Section: Introductionsupporting
confidence: 90%
“…The measurements carried out confirm the findings in [5] regarding thermal and humidity preferences in smart buildings. It might be related to the conditions of indoor environment caused by proper thermal insulation [15] as well as mechanical ventilation managed by the compute software of BMS and other factors [16 -18].…”
Section: Eepes-2022supporting
confidence: 82%
“…Studies of thermal comfort are conducted with the view of determining the impact of physical parameters of air on thermal comfort and broadening the existing experimental base. Dębska [4] examined the thermal comfort of 164 people in an intelligent building and concluded that the level of comfort might not be high enough. Kolkova et al [5] analysed the impact of the heating control system on thermal sensations of laboratory room users.…”
Section: Introductionmentioning
confidence: 99%
“…An example of such research is the research [1,2] carried out in China, which in the first case showed that students prefer cooler temperatures, with the selected temperature range from about 21 o C to about 27 o C, while in the second case, 90% of people believed that they felt thermal comfort. The intelligent building, which was examined by the authors [3,4], provided information in both cases that it meets the thermal expectations of people because the conditions that prevailed at that time were closest to their expectations of comfort. Other interesting studies concern thermal comfort in tropical climates like Australia [5] where the temperature range, according to the respondents, was from 19 o C to 26 o C, Malaysia and Japan [6] where the best temperature was about 25 o C-26 o C degrees, and Bangladesh [7] in which students identified the temperature of 27 o C as the most neutral in their climate zone.…”
Section: Introductionmentioning
confidence: 99%